Does brand personality mediate the link between social media usage and customer buying decisions on telecommunication’s products and services? Evidence from Ghana - Cleophas Attor; Abdul Bashiru Jibril; Miloslava Chovancová (Innovative Marketing, 2022)
Social media marketing has vastly benefitted businesses, including the development of brand identity via solid communication channels. Innovative marketing tools have proven effective among service and non-service-based businesses. This study examines the impact of social media on customer buying decisions via brand personality attributes among telecom products (e.g., mobile phones, sim cards, and data subscriptions) in Ghana. A positivist research paradigm with a non-probability sampling were deployed to achieve study goals. A structured questionnaire was designed to collect the data from subscribers of the telecom giants (MTN, Vodafone, and Airtel-Tigo) in the capital of Ghana through a non-probability sampling technique (snowball/referral method). Both self-administered and online survey (link) were deployed with strict adherence to Covid-19 protocols. A valid data set of 414 (representing 82% of response rate) from 507 responses was received for data processing. PLS-SEM was applied to analyze the study hypothesis. The study identified five main brand personality attributes (i.e., brand sincerity, brand excitement, brand competence, brand sophistication, and brand ruggedness) as mediators of the proposed framework. The study found that brand sincerity, brand excitement, and brand competence played a significant mediation effect on the relationship between social media usage and customer buying decisions, whereas brand sophistication and brand ruggedness did not. The findings suggest that brand management plays an interconnected role in customer decision-making in which brand practitioners should take a keynote regarding their strategic marketing decisions. Finally, the paper recommends that future research consider a mixed approach to offer an in-depth analysis. Acknowledgment This study is supported by Tomas Bata University in Zlin through IGA/FAME /2022/010 Influencer marketing and intercultural differences across generations and IGA/FAME/2021/005-Significant factors in the sustainability of economic growth with a focus on the SME segment. We are grateful to the Editor-in-Chief and the anonymous reviewers for their comments in shaping this manuscript.